Percutaneous catheter drainage for abscess after surgery - Wen-Bo Zhu; Xiao-Hui Zhao; Hai-Liang Li; Chen-Yang Guo; Quan-Jun Yao; Xiang Geng; Ke Zhao; Hong-Tao Hu (Society of Gastrointestinal Intervention, 2022)
Percutaneous abscess drainage (PAD) has been proven to be a safe, effective, and widely used technique for the treatment of patients with abscesses after gastrointestinal surgery. The indications for PAD are expanding and most postoperative abscesses of the gastrointestinal tract are susceptible to PAD. PAD uses various imaging methods, including ultrasound, computed tomography, and several safe and reliable catheter insertion methods.